CURRENT DEVELOPMENT OF HELICOBACTER PYLORI ERADICATION PROTOCOLS - A. Pozdeeva (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
Helicobacter pylori is one of the most common commensal microorganisms in the human body, colonizing up to 60% of the inhabitants on all continents. Some H. pylori strains have acquired virulent properties and their presence can significantly complicate the course of type B atrophic gastritis, gastric ulcer and duodenal ulcer, as well as gastric malignant diseases. In such situations, eradication therapy seems to be pathogenetically justified. In 1996, there were proposed the International Recommendations for standard first-line 7–10-day course triple eradication therapy, including a proton pump inhibitor (PPI), amoxicillin and clarithromycin. Until the beginning of the XXIth century, the International Recommendations has been actively and highly efficiently (up to 90%) used everywhere, but later reports started to emerge regarding a catastrophic decrease in therapeutic outcome (up to 60%). Later, it turned out that the effectiveness of the three-component (triple) therapy directly correlates with the resistance to clarithromycin substantially increased in recent decades, which necessitated generation of new schemes for H. pylori elimination. The results of various schemes for H. pylori eradication were analyzed, including variants of modified triple therapy associated with the inclusion of new drugs or prolonged duration of the therapeutic protocol. In particular, it was proposed to replace amoxicillin with metronidazole. However, further studies have shown that the combination of clarithromycin with amoxicillin seems to be preferable due to the high level of H. pylori resistance to metronidazole recorded in many countries. Attempts to use probiotics in parallel, particularly cultures of various Lactobacillus species, were analyzed, which increases the level of eradication during standard triple therapy from 61.5% to 81.6%, and significantly reduces the severity of side effects. It has been shown that a promising approach to increase the effectiveness of 7-day first-line therapy schemes with clarithromycin is to use modern effective PPIs (for example, esomeprazole or rabeprazole). The scheme of modified sequential therapy with the replacement of clarithromycin with tetracycline or levofloxacin, which has shown high efficiency has been considered. A variant of standard triple therapy modified into quadrotherapy by adding metronidazole or tinidazole was analyzed. It has been shown that the sequential therapy scheme is ineffective for eradication of multidrug-resistant strains. Ideally, the treatment of bacterial infections should be based on endoscopic sampling of gastric mucosa biopsies, followed by microbiological determination of in vitro antibacterial drug sensitivity in bacterial isolates.